GDI626 : Illustration for independent publishing / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2021)
Self-publishing or freelance job are becoming popular among the artist nowadays, especially when it can be hard to get their foot in the door with mainstream publishers. At the core, self-publishing culture offers freedom from the editorial restrictions exerted by mainstream publishing and print distribution processess, whilst also circumventing gallery systems to reach new audiences. Publication is to make public. Authorship is entirely attributed by the artist, with ideas freely or affordably exchanged. Artists will be able to make profit by themselves without going through the process of middle person. In this course, self-publishing is not only focused on industrial format printed media, but able to recognize the new, cheaper materials in printing technologies, explore the potential of interactive digital media like e-books or digital art commissions and find out the way to distribute the works. Students also will be exposed to the various profession in the art industry, able to estimate their own publication cost and commission rate of their artworks based on quality they provided.